2017
DOI: 10.1103/physrevb.96.075139
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and spin ordering physics of the Mn3O4 spinel

Abstract: Motivated by recent experiments, we present a comprehensive theoretical study of the geometrically frustrated strongly correlated magnetic insulator Mn3O4 spinel oxide based on a microscopic Hamiltonian involving lattice, spin and orbital degrees of freedom. Possessing the physics of degenerate eg orbitals, this system shows a strong Jahn-Teller effect at high temperatures. Further, careful attention is paid to the special nature of the superexchange physics arising from the 90 o Mn-O-Mn bonding angle. The Jah… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Therefore, the exchange interaction of Mn 3+ -Mn 3+ exhibites strongly antiferromagnetic in ab-plane, and J c BB is weak along the c-axis due to elongation of BO6 octahedra. With the mechanism such as interplay of JAB and JBB, a collinear Néel phase can not appear in Mn3O4, while a noncollinear ferrimagnetic YK phase presents instead [21,41]. However, JBB is not strong compared with JAB in MnV2O4 and spins of V 3+ ions can be aligned parallel to each other to produce collinear long-range ordering, so the spins of Mn 3+ remain disordered but V 3+ ordered at T1 in Mn1+xV2-xO4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the exchange interaction of Mn 3+ -Mn 3+ exhibites strongly antiferromagnetic in ab-plane, and J c BB is weak along the c-axis due to elongation of BO6 octahedra. With the mechanism such as interplay of JAB and JBB, a collinear Néel phase can not appear in Mn3O4, while a noncollinear ferrimagnetic YK phase presents instead [21,41]. However, JBB is not strong compared with JAB in MnV2O4 and spins of V 3+ ions can be aligned parallel to each other to produce collinear long-range ordering, so the spins of Mn 3+ remain disordered but V 3+ ordered at T1 in Mn1+xV2-xO4.…”
Section: Discussionmentioning
confidence: 99%
“…Since the antiferromagnetic exchange energy of Mn 3+ -Mn 3+ ( J ab BB ) is much stronger than the Mn 3+ -Mn 2+ coupling (JAB), a collinear magnetic structure can't form under frustration. There are two paths to achieve magnetic interactions between nearestneighbor Mn 3+ ions [40,41]: i) the direct exchange interactions between the neighboring t2g orbitals which are strongly antiferromagnetic; ii) the superexchange interaction involving neighboring eg electrons and middle oxygen's 2p orbital, which is weakly ferromagnetic. Therefore, the exchange interaction of Mn 3+ -Mn 3+ exhibites strongly antiferromagnetic in ab-plane, and J c BB is weak along the c-axis due to elongation of BO6 octahedra.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to test these predictions numerically by looking for signatures in, for instance, exact diagonalization (ED) studies of small clusters. Extending our work to the case of spinel systems (in which both A and B sites are magnetic) should be interesting, as magnetisation plateaux 52 and spin liquid ground states 53,54 in such systems are under investigation. Finally, it will be challenging to adapt either the functional RG method 55 or the renormalisation group method used recently in studying the m/m s = 1/3 plateau of the kagome system 15 to the plateaux we have predicted here for the pyrochlore.…”
Section: Spin-parity and Magnetisation Plateauxmentioning
confidence: 99%
“…The exchange couplings of Mn 3 O 4 have been quantitatively estimated from the spin wave excitations measured by neutron scattering experiments, and have demonstrated that the exchange interactions are determined by the direct orbital overlap and the 90 • superexchange coupling between two Mn 3+ ions via an oxygen bridge. 10,12 Meanwhile, Mn 3 O 4 always exhibits insulating behavior with a band gap of about 2.0 eV. [13][14][15] Mn 3 O 4 is a challenging system to tackle by first- principles calculations, because strong electron correlations are combined with multiple degrees of freedom such as spin, orbital, charge, and lattice.…”
Section: Introductionmentioning
confidence: 99%